Prevalence of Pharyngitis and Tonsilitis among Children (Medical Forum Monthly, 2024)
Objective: Tonsillitis and pharyngitis are very common medical problems especially among the children. Tonsillitis affects mostly children between the age of 3-5 years because this is when their tonsils are in their most active stage, fighting infectious. When the child grown older, the tonsils will shrink and infection will become less common. Tonsillopharyngitis is one of the most common infections worldwide especially in children and young adults. Viruses are often involved in children younger than 5 years of age and a bacterial etiology is more usual after this age.Study Design: Cross Sectional Study.Place and Duration of Study: This Study was conducted at the Department of Microbiology, Basic Medical Sciences Institute, Jinnah Postgraduate Medical Centre, Karachi from Dec. 2008 to June 2009.Materials and Methods: A total of 300 subjects (250 suspected children and 50 healthy children as control) of age ≤5-15 years, were included and this age group was again divided into three groups: ≤5-8 years, 9-12 years and 13-15 years respectively.The throat swab was taken in duplicate, for that the care was done, not to touch the tongue of sides of the mouth cavity, the swab was taken from the posterior pharyngeal wall. The first swab was for the performance of Rapid Strep Test according to the principle and procedure mentioned and the 2nd swab for the culture and further processing in the microbiological laboratory.Result: The percentage of isolated cases positive for GABHS. Out of 250 suspected cases 24 (9.6%) were positive for GABHS while 226 (90.4%) were negative for GABHS. The age wise distribution of the infection among ≥5-8 years, it was 13 (13.7%), among the age of 9-12 years it was 6 (6.2%) and among the age group of 13-15 years it was 5 (8.6%). Distribution of tonsillitis and pharyngitis among 166 male children, 4 (2.4%) were positive for tonsillitis, while 11 (6.6%) were positive for pharyngitis, while in female children, which 84 in total, 3 (3.6%) were positive for tonsillitis and 6 (7.1%) were positive for pharyngitis.Conclusion: Group A beta hemolytic Streptococcal infection of throat constitute one of the major public health problems due to its post infectious complications. The data obtained provides information about the commonly prevalent bacteriological agent in pharyngitis and tonsillitis. Furthermore, it helps to outline the strategy towards appropriate therapy. It has also been concluded from this study that pharyngitis is more prevalenct than tonsillitis.